﻿Influence of vitamin D on fracture reduction among older adults: a discussion of recent meta-analysis findings - Bischoff-Ferrari, Heike A. (Osteologie, 2019)
Recent meta-analyses on vitamin D and fracture reduction have led physicians and patients to question current guidelines on vitamin D. In this review of four recent meta-analyses, we summarize these meta-analyses with regard to target group and relevance to current guidelines. Importantly, two of the recent meta-analyses target adults age 50 years and older without osteoporosis and vitamin D deficiency where trial data is still very limited and does not reflect the target group of older adults age 65 and older vulnerable to both osteoporosis and vitamin D deficiency. One other meta-analysis has a focus on vitamin D plus calcium with significant benefits for both total and hip fractures, and one excludes these trials and shows no benefit plus has been questioned for several limitations with regard to study design. In summary, for older adults at increased risk for fractures and/or vitamin D deficiency, it is still reasonable to take 800 to 1000 IU vitamin D per day, following current recommendations. Reducing the risk of fractures among vulnerable older adults age 65 and older, at risk of vitamin D deficiency and fractures, remains a major public health target.
Keywords: Vitamin D; fractures; meta-analysis